SUPGUARD - CIPEEX 2025 (CIPEEX, 2026)
SupGuard is an application focused on public safety in the city of Anápolis, Goiás. It aims to inform and protect citizens through real-time notifications, risk-area mapping, and collaborative reports on criminal incidents. The system integrates a robust Flask backend and a PostgreSQL database, ensuring scalability and accuracy. With an intuitive interface, the app fosters community engagement and provides a clear visualization of urban safety data.
Keywords: software engineering; Security